The Effects of Textual Enhancement Technique on the Acquisition of Comparison Degrees of Indonesian Secondary School Students - Sugiyanti, Luluk; Wati, Ning Setio (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2022)
Textual enhancement technique is a technique that refers to the specific linguistics target through the text. The main purpose of this study was to determine whether the technique of using textual enhancement affects the students' grammar mastery, especially in the comparison degree material. Comparison degree is the process of comparing things, persons, or places through the level of quality, or relation and is formed by adjectives and adverbs. This research method was quantitative in the form of a pre-experimental design. There were 40 Indonesian Secondary School students participating in the study. They were randomly assigned to one control and one experimental group by 20 participants in each group. During the four-week period of the current study, the participants received the instructions and treatment. Then the experimental group was exposed to comparison degrees presented with four different textual enhancement techniques. The control group was exposed to comparison degrees used with a different technique (traditional technique) in teaching activities. The data were collected after instructional sessions during the four weeks through paragraphs focusing on comparison degrees production written by the participants. After the treatment, a comparison degree was also administered to the control group, as a posttest. The results showed that the textual enhancement technique can be an alternative strategy in learning English, significantly affecting Indonesian secondary school students’ comparison degrees.